Analisis Komparasi Tingkat Kesehatan dan Gejala Financial Distress pada Bank Umum Syariah Indonesia dan Malaysia Periode 2018-2022 - Avisha Yustikasari; Muhtadin Amri (Falahiya: Journal of Islamic Banking and Finance, 2025)
Introduction: This research aims to analyze the level of bank health and symptoms of financial distress in Indonesian and Malaysian Sharia Banks for 2018-2022 period. Research Methods: The research method is quantitative descriptive using RGEC, Springate S-Score and Zmijewski X-Score. Data analysis using Normality Test, Sign-Wilcoxon Difference Test and Mann Whitney Test. Data used is from the bank's annual financial and GCG report for the 2018-2022 period. Results: Level of bank health using RGEC analysis shows Indonesian Sharia Commercial Banks in "Healthy" condition with percentage of 73%. Likewise, Malaysian Sharia Commercial Banks are in "Healthy" condition with percentage of 81%. This indicates that the health level of Malaysian BUS is better than Indonesian BUS. Measuring the level of financial distress using Springate S-Score analysis shows that Indonesian and Malaysian BUS are in healthy condition. Conclusion: The Sign-Wilcoxon difference test show that when comparing the level of soundness of Islamic banks there is a difference in the NPF and BOPO ratios, while there is no difference in the ROA ratio. Meanwhile, in the FDR using the Mann Whitney test, it is known that there are differences, ROE and CAR ratios of Sharia Commercial Banks there are no differences.